Acceleration and novelty: community restoration speeds recovery and transforms species composition in Andean cloud forest. Issue 1 (January 2016) - Wilson, Sarah Jane; Rhemtulla, Jeanine M.
Abstract: Community‐based tropical forest restoration projects, often promoted as a win‐win solution for local communities and the environment, have increased dramatically in number in the past decade. Many such projects are underway in Andean cloud forests, which, given their extremely high biodiversity and history of extensive clearing, are understudied. This study investigates the efficacy of community‐based tree‐planting projects to accelerate cloud forest recovery, as compared to unassisted natural regeneration. This study takes place in northwest Andean Ecuador, where the majority of the original, highly diverse cloud forests have been cleared, in five communities that initiated tree‐planting projects to restore forests in 2003. In 2011, we identified tree species along transects in planted forests ( n = 5), naturally regenerating forests ( n = 5), and primary forests ( n = 5). We also surveyed 120 households about their restoration methods, tree preferences, and forest uses. We found that tree diversity was higher in planted than in unplanted secondary forest, but both were less diverse than primary forests. Ordination analysis showed that all three forests had distinct species compositions, although planted forests shared more species with primary forests than did unplanted forests. Planted forests also contained more animal‐dispersed species in both the planted canopy and in the unplanted, regenerating understory than unplanted forests, and contained the highest proportion of species with use value for local people. While restoring forest increased biodiversity and accelerated forest recovery, restored forests may also represent novel ecosystems that are distinct from the region's previous ecosystems and, given their usefulness to people, are likely to be more common in the future.